Spherical Mesoporous SBA‐15‐Supported CoP Nanoparticles as Robust Selective CO2Reduction and H2‐Generating Catalyst under Visible Light. Issue 21 (11th September 2020) - Fu, Zi‐Cheng; Moore, Joshua T.; Yang, Zi‐Xin; Hu, Jia‐Jun; Fu, Wen‐Fu
Abstract: The highly active spherical hybrid catalysts with diameters of 3–8 μm for robust selective CO2 photoreduction and hydrogen production by switching solvent, CoP/(i)s‐SBA‐15 and CoP/(o)s‐SBA‐15, were in situ synthesized for the first time by incorporating CoP nanoparticles on the interior and outside of the spherical mesoporous Santa Barbara Amorphous (s‐SBA)‐type material s‐SBA‐15. CoP/(i)s‐SBA‐15 has a larger pore diameter of ∼9.5 nm, relative to ∼5.7 nm of CoP/(o)s‐SBA‐15, and a calculated Brunauer‐Emmett‐Teller surface area of ∼214 m 2  g −1 compared with ∼336 m 2  g −1 for the latter. In comparison with bare CoP, the composites exhibited excellent catalytic CO‐ and H2 ‐generating performance with product selectivity of up to 76.3 % and 99.9 % through switching solvents containing Ru‐based photosensitizer under ambient conditions, respectively. The influences of various solvents and electron donors, as well as the amounts of H2 O, and catalyst on reaction kinetics for CO2 reduction and H2 production, and intrinsic properties of both catalysts were investigated and compared. Abstract : CoP for photocatalysis : Sphericalmesoporous SBA‐15‐supported CoP nanoparticlecatalysts tuning the highly efficient photocatalytic CO‐and H2 ‐generating pathways with product selectivity of up to 76.3 %and 99.9 % through switching solvent, respectively, were in situ fabricated by CoP embedded on the surface and interior of the porous s‐SBA‐15.